Pap smear: understanding of rural women about the purpose and access - Igho Leonardo do Nascimento Carvalho; Renata Barbosa Nunes; Isaura Danielle Borges de Sousa; Rose Danielle de Carvalho Batista; Antonia Sylca de Jesus Sousa; Caroline da Silva Sousa (Rev Rene)
Objective: to describe the understanding of rural women about the purpose and access to Pap smear. Methods: qualitative study conducted with 15 women. Data collection was carried out through a semi-structured interview script, by adopting content analysis. Results: the study found that women had insufficient understanding about the reason to perform the examination, both in the matter of prevention and regarding diagnosis of cervical cancer. Women have also demonstrated difficulties to perform the examination by the difficult access to the cytological examination and by the little frequency of the Family Health Strategy team in going the rural communities evaluated. Conclusion: the understanding of the purpose of Pap smear is insufficient and access is inappropriate. This condition is a risk to the onset of cervical cancer in rural women.